RETRACTED: Teaching in Rural Indonesian Schools: Teachers’ Challenges - Mia Febriana; Joko Nurkamto; Dewi Rochsantiningsih; Anggri Muhtia (International Journal of Language Teaching and Education, 2018)
This article has been retracted: please see IJoLTe publication etichs on duties of authors, section Multiple, Redundant or Concurrent Publication (https://online-journal.unja.ac.id/index.php/IJoLTE/Ethics) This article has been retracted as the initiative of the editor in chief as the result of violations of publication ethics. The article doing multiple submission. If you want to get the article, please visit to: https://ijmmu.com/index.php/ijmmu/article/view/305 International Journal of Language Teaching and Education takes a very strong view on this matter and apologies are offered to readers of the journal for this problems. Regards, IJoLTe Team